SGLT2-inhibitors are effective and safe in the elderly: The SOLD study. (September 2022) - Lunati, Maria Elena; Cimino, Vincenzo; Gandolfi, Alessandra; Trevisan, Matteo; Montefusco, Laura; Pastore, Ida; Pace, Camilla; Betella, Nazarena; Favacchio, Giuseppe; Bulgheroni, Monica; Bucciarelli, Loredana; Massari, Giulia; et al.
Abstract: Background and aims: Sodium-glucose co-transporter-2 inhibitors (SGLT2i) may have important benefits for the elderly with type 2 diabetes (T2D), however some safety concerns still limit their use in patients over 70 years of age. The SOLD study ( SGLT2i in Older Diabetic patients ) is a multicenter study, aimed to evaluate the effectiveness and safety of SGLT2i in the older diabetic patients in a real-life setting. Materials and methods: We analyzed a population of 739 adults (mean age 75.4 ± 3.9 years, M/F 420/319) with T2D, which started a SGLT2i-based treatment after the age of 70, with at least one year of follow-up. Data were collected at baseline, at 6 and 12 months of follow-up. Results: SGLT2i (37.5% Empagliflozin, 35.7% Dapagliflozin, 26.1% Canagliflozin, 0.7% Ertugliflozin) were an add-on therapy to Metformin in 88.6%, to basal insulin in 36.1% and to other antidiabetic drugs in 29.6% of cases. 565 subjects completed the follow up, while 174 (23.5%) discontinued treatment due to adverse events which were SGLT2i related. A statistically significant reduction of glycated hemoglobin (baseline vs 12 months: 7.8 ± 1.1 vs 7.1 ± 0.8%, p < 0.001) and body mass index values (baseline vs 12 months: 29.2 ± 4.7 vs 28.1 ± 4.5 kg/m 2, p < 0.001) were evident during follow-up. Overall, estimated glomerular filtration rate remained stable over time, with significant reduction of urinary albumin excretion. In the subgroup of patients which were ≥ 80 years, a significant improvement in glycated hemoglobin values without renal function alterations was evident. Overall discontinuation rate during the follow-up period was different across age groups, being urinary tract infections and worsening of renal function the most common cause. Conclusion: SGLT2i are well-tolerated and safe in the elderly and appear as an effective therapeutic option, though some caution is also suggested, especially in more fragile subjects. Graphical Abstract: ga1